Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content: 1. The Degree of Using Infographics in Presenting & Presenting data in Public Education Agency Programs from General Supervisors’ Perspective in the Ministry of Education in The Kingdom of Saudi Arabia Mrs. Wardah Ali H. Al-Razouq , Prof. Ajlan Mohammed H. Al-Shehri 2. Level of Including Values in Arabic Language Course for 3G Primary, in the Kingdom of Saudi Arabia, in Light of the Cross-Cutting Dimensions of the Public Education Curricula Standards Mrs. Taghreed Saeed Al-Rasasimah, Co-Prof. Abeer Mohammed Al-Arfaj 3. The Impact of Electronic Educational Broadcasting on the Development of English Listening Skills for Primary Students Sixth Grade Mrs. Seetah Mohammed Abdullah Al-Sahali, Prof. Ajlan Mohammed Al-Shehri 4. The Effectiveness of Instructional Scaffolding Strategy in Developing Social Interaction of Eleventh-Grade Students in The Subject of History Dr. Sattar Jabbar Haji, Dr. Imad Ali Safar , Asst-Lecturer Dilkhaz Shekhomar Mostafa 5. The Degree of Possessing E-Learning Skills by Secondary Stage Teachers from School Principals’ Perspectives in Amman Governorate Mrs. Hasnah Abdel-Hafeez Al-Ashush 6. Attitudes of teachers and students’ guardians towards the application of the "Trimester" in The Kingdom of Saudi Arabia Mrs. Najwa Mohammed A. Al-Shammari 7. A Literature Review on Fostering Teaching English as Foreign Language (EFL) Using Digital Activities Mrs. Faten Ahmed Saeed Alghamdi , Co-Prof. Mai Mohammed Lutfi Alnajami